Palin parent-child interaction therapy - Kelman, Elaine (Henry Stewart Talks, 2016)
Multifactorial model of onset & development of stuttering, Therapeutic approach: core values, Risk factors for young children who stutter, Screening for vulnerability to persistence and appropriate care pathways, Assessment of stuttering, Principles of Palin parent-child interaction (PCI) therapy, Using video analysis in PCI therapy, Three main strands of PCI therapy: interaction, family, child (strategies)